Uncovering a motherhood advantage: How parenthood impacts perceptions of the meaning of work and work outcomes. - Liao, Huiyao; Allen, Tammy D.; Liu, Zhaopeng; Ptashnik, Thomas; Wu, I-Heng (Ray) (Journal of Applied Psychology, 2026)
which captures individuals' cognitive orientation to construe work meaning through its symbolic relevance to family. Specifically, it refers to individuals' perception of their work as a vehicle for expressing their professional ethics and principles to their family and serving as role models. We then draw upon self-construal theory to theorize that, in comparison to nonparents, working parents are more likely to develop higher FCSMW. We further posit that the positive association between parental status and FCSMW is more pronounced for women than for men. Additionally, we argue that FCSMW positively correlates with employees' display of exemplary behaviors at work, such as increased work effort and organizational citizenship behavior. Finally, we propose that the indirect effects of parental status on work outcomes via FCSMW are stronger for women than men. To assess our proposed model, we first developed and validated a scale for measuring FCSMW. We then tested our hypotheses using three sets of data: two multisource, field samples from China, and one field sample from the United States, all of which supported our hypotheses. (PsycInfo Database Record (c) 2026 APA, all rights reserved).